Characteristics and determinants of ambient volatile organic compounds in primary schools. Issue 11 (26th October 2016) - Wang, Yu-Chun; Lin, Chitsan; Lin, Yu-Kai; Wang, Ya-Fen; Weng, Wei-Huang; Kuo, Yi-Ming
Abstract : This study evaluates the effects of a sampling strategy that includes the sampling season, time period, ambient environment, and location on determining the concentrations and species of ambient volatile organic compounds (VOCs) that may affect children in primary schools. Abstract : This study evaluates the effects of a sampling strategy that includes the sampling season, time period, ambient environment, and location on determining the concentrations and species of ambient volatile organic compounds (VOCs) that may affect children in primary schools. Air samples were collected from playgrounds in primary schools, with four sites near an oil refinery plant in Taoyuan and two sites in Zhongli (one site near a bus terminal and the other site in a suburban area) in Taiwan. The samples were obtained on eight occasions from August 2010 to June 2011. One sample was collected from 09:00 to 11:00 and the other was collected from 13:00 to 15:00 on each occasion using passive flow controller canisters (40 mL min −1 flow rate) assembled with silica-coated stainless steel. The United States Environmental Protection Agency Method TO-15 with Photochemical Assessment Monitoring System and Urban Air Toxics standards was used to analyze the samples. The ratios of benzene, toluene, ethylbenzene, and xylenes (BTEXs) were also estimated. This study found that the sampling location and wind direction are the main determinants to monitor the concentrations and species of ambient VOCs, and the effects from the sampling season and time period are minor. Alkane, ketone, and aromatics have been ranked as the top three categories with high concentrations, and toluene, 2-butanone, and acetone have been detected with the highest concentrations among the investigated VOCs. Several VOCs emitted from stationary sources, including propane, isoprene, n -decane, chloromethane, chloroethene, chloroethane and 1, 2-dichloroethane, were detected only in Taoyuan. Higher concentrations of VOC species associated with automobiles and common community sources were detected in Zhongli but not in Taoyuan. Among BTEXs ratios, toluene/ethylbenzene ratios were as high as 31.52 (standard deviation [S.D.] = 13.53) in Taoyuan and 13.66 (S.D. = 3.87) in Zhongli. Toluene/benzene ratios were as high as 15.7 in Taoyuan and 4.30 in Zhongli. This study suggests that the susceptible population exposed to ambient VOCs should be considered in planning public service facilities and the presence of VOCs should be investigated regularly.